Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/atmos13122022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal Exposure to Household Air Pollution from Multiple Sources on Risk of Preterm Birth

Abstract: Prenatal exposure to air pollution has been suggested as a major risk factor for preterm birth (PTB). This study aimed to explore the independent and joint effects of prenatal exposure to multiple household air pollution (HAP) sources on PTB. This study involved 63,038 mother–child pairs from the Longhua Child Cohort Study in 2017. A series of logistic regression analyses on associations of environmental tobacco smoke (ETS), cooking oil fumes (COFs), burning mosquito coils (BMCs), indoor burning incense (IBI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Additionally, exposure to ETS during pregnancy was associated with an increased risk of preterm birth (PTB) both before and after adjusting for potential confounders. Liu et al [ 39 ] also found an increased risk of PTB among mothers with prenatal exposure to ETS, and the risk increased with the average level of daily ETS exposure. Surprisingly, the increased risk of PTB due to ETS during pregnancy was observed only among mothers who were more educated [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, exposure to ETS during pregnancy was associated with an increased risk of preterm birth (PTB) both before and after adjusting for potential confounders. Liu et al [ 39 ] also found an increased risk of PTB among mothers with prenatal exposure to ETS, and the risk increased with the average level of daily ETS exposure. Surprisingly, the increased risk of PTB due to ETS during pregnancy was observed only among mothers who were more educated [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, the increased risk of PTB due to ETS during pregnancy was observed only among mothers who were more educated [ 28 ]. This might be because most participating mothers were well-educated, and there were significant differences in maternal educational level between PTBs and FTBs [ 39 ]. Liu et al [ 32 ] also pointed out that paternal smoking during gestation had a significant association with PTB, and the association was more obvious in boys and children with old (≥34-year-old) mothers.…”
Section: Methodsmentioning
confidence: 99%